Aspek Teologis dan Aplikatif Dasa Titah - Rully Solomon Runturambi (Sekolah Tinggi Teologi Berita Hidup, 2019)
Believers today are eager to explore the Bible, especially the New Testament, because they believed that the Old Testament is no longer valid in the lives of believers. The discussion in this paper examines the importance of the Decalogue and its application to believers in the present. The Ten Commandments are the culmination (climax) of all the books, centers and themes of the extraordinary book that ever existed. The Ten Commandments are the basis of all Bible themes. The Ten Commandments are the highest foundation of God's law. Many verses in the Bible (Old and New Testaments) are citation extensions of the Ten Commandments. God's command is a measure that enables us to know whether we are on the path that is in accordance with His desires or we are deviating. As John warned in 1 John 3: 4